2013
DOI: 10.1111/joor.12106
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gag reflex on dental attendance, dental anxiety, self‐reported temporomandibular disorders and prosthetic restorations

Abstract: To assess the influence of gag reflex severity, assessed according to the short form of the patient part of Gagging Problem Assessment Questionnaire (GPA-pa SF), on the dental attendance, dental anxiety, self-reported temporomandibular disorder (TMD) symptoms and presence of prosthetic restorations among patients requiring prosthodontic treatment in Turkey. A total of 505 patients (305 women; mean age: 46·35 years, SD: 28·2 years) undergoing dental examination were administered a questionnaire containing quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 21 publications
1
27
1
6
Order By: Relevance
“…This survey identifies patients with a significant gagging problem, but again relies on invasive prob. There is also a nine question version of the GPA that can be completed by the patient that is not complimented by invasive probing, and this has been shown to be reliable and valid [13][14][15]. The shortened GPA contains questions that have patients estimate the level of gagging induced by 'feeling a mirror between posterior teeth', 'taking an impression of the upper jaw', and 'taking an impression of the lower jaw'.…”
Section: Predictive Gagging Survey Gagging Severity Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…This survey identifies patients with a significant gagging problem, but again relies on invasive prob. There is also a nine question version of the GPA that can be completed by the patient that is not complimented by invasive probing, and this has been shown to be reliable and valid [13][14][15]. The shortened GPA contains questions that have patients estimate the level of gagging induced by 'feeling a mirror between posterior teeth', 'taking an impression of the upper jaw', and 'taking an impression of the lower jaw'.…”
Section: Predictive Gagging Survey Gagging Severity Indexmentioning
confidence: 99%
“…A case report found that intranasal midazolam, a benzodiazepine, reduced the patient's experience of the gag reflex [25]. Additionally, some case reports show that using chemical stimulation of the oral palate with a sodium chloride solution can temporarily reduce the gag reflex [26][27][28], although a controlled study failed to find a significant effect of table salt in reducing the gag reflex [13]. It may also be interesting to examine whether a stronger gag reflex is correlated with increased orofacial pain that is itself related to third molar extraction [29].…”
Section: Predictive Gagging Survey Gagging Severity Indexmentioning
confidence: 99%
“…Exaggerated gag reflex may lead to problems during clinical stages of fabrication and during wearing of removable complete and partial prostheses . An unusually active gag reflex upsets the patient and consequently may lead to avoidance of routine dental treatment, poor oral hygiene, and tooth loss …”
mentioning
confidence: 99%
“…4 HGR may cause selfconsciousness, embarrassment, avoidance of dental treatment, fear, anxiety, and a negative impact on overall quality of life. [5][6][7][8][9] Various behavioral and pharmacological methods have been suggested to reduce HGR in dental patients. [10][11][12][13][14][15][16] It has been claimed that nitrous oxide and oxygen sedation (N 2 O) is able to completely obtund the HGR 17 ; however, we searched the literature and could find no study in which this was proven.…”
mentioning
confidence: 99%